EFL STUDENTS' CHALLENGES IN LEARNING SPEAKING SKILLS: A CASE STUDY IN MECHANICAL ENGINEERING DEPARTMENT - Ratnasari, Aisha Ganesh (Journal of Foreign Language Teaching and Learning, 2020)
Nowadays, speaking mastery is important due to the position of English as a universal language (Nazara, 2011). This research used a case study as the research design, which aimed to answer the research questions such as challenges faced by the students in learning speaking skills and strategies implemented by the students to overcome the challenges. There were three participants in this research, namely two Mechanical Engineering Department, Olaf and Elsa, and one English teacher in the Mechanical Engineering Department, Anna. The data obtained were through interviews and students? speaking grades through classroom presentations. The result showed four challenges, such as lack of vocabulary, nervousness, unsupportive environment, and lack of grammar knowledge. Besides, there were five strategies, such as codeswitching, seeing the audiences as the statues, using google translate machines, making a personal approach to the English teacher, and encouraging self.